Do goodwill impairments affect audit opinions? Evidence from China - Ziye He; Dong Chen; Jianxin Tang (China Journal of Accounting Research, 2021)
There has been a steady growth of goodwill impairments in the Chinese stock market since the adoption of the impairment approach in accounting. The influence of goodwill impairments on a firm's financial position and profitability give reason to doubt its current and future performance. We examine whether auditors, as a crucial external monitor, identify the information risks of goodwill impairments and express their concerns about financial reporting quality in their audit opinions. Using a sample of firms listed on China's A-share market from 2007 to 2017, we test the association between goodwill impairments and the type of audit opinion received in the same financial period. Our findings are as follows. First, the probability of receiving a modified opinion increases with the amount of goodwill impairments. Second, the positive association between goodwill impairments and modified audit opinions is driven primarily by earnings management risks. Third, this positive association is more salient when auditors are industry experts and there is no auditor-client mismatch. Fourth, auditors are more sensitive to the amount of goodwill impairments than to their mere existence. Overall, we document that auditors perceive goodwill impairments as a signal of information risks and communicate their concerns to investors to avoid litigation.
Keywords: M41; M42; 650; Audit opinions; Earnings management; Economic fundamentals; Goodwill impairments; Material misstatements